Does poverty alleviation help enhance social investment? The case of South Korea. Issue 1 (2nd January 2022) - Han, Sam; Gao, Qin
ABSTRACT: Using the 2015 Korean Welfare Panel Study data and a regression discontinuity design, this study examines the effects of the National Basic Livelihood Security System (NBLSS) participation on social investment through evaluating its impact on changes in family consumption patterns. We find that NBLSS participation was associated with increased educational expenditures. The effects were larger for households with an elementary or junior-high school student than those with a high school or college student. We also find that NBLSS participation reduced medical expenditures for households with seniors, members with chronic diseases, and members with a physical disability, most likely due to the in-kind healthcare services.